Rooting Response of Coppice Shoot Nodal Cuttings of Eucalyptus Hybrid as Influenced by Season - Barshi, Meena (Indian Forester, 1998)
Seasonal variations in coppice shoot production capacity and rooting/sprouting behaviour of coppiced shoot nodal cuttings was studied in adult Eucalyptus hybrid trees. The results reveal that the best period of coppicing is FebruarylMarch and the best period of excision of coppice shoots and planting is May-June. The best treatment for maximum vegetative propagule production is Indole butyric acid 4000 ppm.